Narrator czy… poeta oralny? Mickiewiczowski „Powrót taty” w opracowaniu muzycznym Henryka Jareckiego i Jana Gołębiowskiego - Piotrowska, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article discusses the opera-ballad Powrót taty (Father’s return) in a musical edition by Henryk Jarecki with a libretto by Jan Gołębiowski. Its goal is to present the manners of building the character and the narrative. Apart from the characteristic features of a ballad, the text also discusses the category of an oral poet, a “storyteller” and the dialogue relation (“speaking” instead of “talking”.) These are the means that gave Mickiewicz’s ballad a new dimension. Helpful in its reception are texts on cultural practices, especially those referring to oral culture (compare with e.g. Jack Goody, Albert B. Lord, Eric A. Havelock, Walter J. Ong.).